2018
DOI: 10.1021/acsnano.8b04443
|View full text |Cite
|
Sign up to set email alerts
|

Directed Assembly of Au-Tipped 1D Inorganic Nanostructures via Nanolithographic Docking

Abstract: Controlled assembly of nanostructures is a key challenge in nanotechnology. In this work, we introduce an approach for the controlled assembly of 1D nanodumbbellsAu-tipped semiconductor nanorodsinto arbitrary 2D higher architectures, by their chemical docking to nanopatterned functionalities. We realized the docking functionalities via nanoimprinted metallic nanodots functionalized with an organic monolayer, whose terminal thiol groups chemically bind the nanodumbbell tips. We demonstrated that the functiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…Weak chemical interactions allow enough mobility for the 1D-nanoobjects to align with the binding sites, and the distances between neighboring binding sites should be slightly smaller than the length of the 1D-nanoobjects to maximize the possibility of bridging two binding site by a single 1D-nanoobject. Many different 1D-nanoobjects including DNA origami, 111,112 CNT 113 and inorganic nanorods 114 have been assembled by this technique. Yan et al reported the assembly of thiolated DNA origami nanotubes by directly attaching the tubes to gold islands on the substrate through thiol-Au bonds (Fig.…”
Section: Interconnecting Patterned Surface With 1d-nanoobjectsmentioning
confidence: 99%
“…Weak chemical interactions allow enough mobility for the 1D-nanoobjects to align with the binding sites, and the distances between neighboring binding sites should be slightly smaller than the length of the 1D-nanoobjects to maximize the possibility of bridging two binding site by a single 1D-nanoobject. Many different 1D-nanoobjects including DNA origami, 111,112 CNT 113 and inorganic nanorods 114 have been assembled by this technique. Yan et al reported the assembly of thiolated DNA origami nanotubes by directly attaching the tubes to gold islands on the substrate through thiol-Au bonds (Fig.…”
Section: Interconnecting Patterned Surface With 1d-nanoobjectsmentioning
confidence: 99%
“…13 CdS-Au nano-dumbbells self-assemble on pre-fabricated AuPd NPs on a Si substrate ('nanolithographic docking'). 274 Reproduced with permission from the American Chemical Society, copyright 2018.…”
Section: Catalysismentioning
confidence: 99%
“…Studying the fabrication of nanometer scale structures with at least one dimension in the size ranging between 1 and 100 nm is termed as nano-lithography with different varieties of the nano-imprint, namely, optical, multi-photon, scanning probe lithography, and electron beam. 59,60 In general, lithography refers to the procedure of printing the intended form or structure on light sensitive materials, which eliminates a part of the materials for creating the intended shape and structure in a selective manner. 61 3.1.3.…”
Section: Top-down Synthesismentioning
confidence: 99%